Pengaruh work motivation, work-life balance, dan career development terhadap organizational commitment melalui mediasi job satisfaction pada karyawan PT XYZ di Jakarta Selatan - Callista Vanessa Xenia; Yanuar Yanuar (Universitas Tarumanagara, 2026)
This study aims to determine the effect of work motivation, work-life balance, and career development on organizational commitment through the mediation of job satisfaction among employees of PT XYZ in South Jakarta. The sampling technique used was non-probability sampling with a purposive sampling approach. The respondents of this study consisted of 125 employees working at PT XYZ in South Jakarta as respondents. Data analysis was conducted using SmartPLS version 4.1. The results revealed that work motivation and work-life balance did not have a significant effect on organizational commitment, while career development had a positive and significant effect on organizational commitment. Job satisfaction was also found to have a positive and significant influence on job satisfaction. Furthermore, job satisfaction was found to mediate the relationship between work motivation and organizational commitment. The managerial implications of this study suggest that PT XYZ should strengthen career development program through regular training, mentoring, and clear promotion paths to strengthen employee commitment. The company also needs to review its compensation and incentive systems, involve employees in decision making to enhance a sense of ownership and provide recognition for achievements and collaborative activites to enhance meaning and engagement at work. Penelitian ini bertujuan untuk mengetahui pengaruh work motivation, work-life balance, dan career development terhadap organizational commitment melalui mediasi job satisfaction pada karyawan PT XYZ di Jakarta Selatan. Teknik pengambilan sampel yang digunakan adalah non-probability sampling dengan pendekatan purposive sampling. Responden dalam penelitian ini adalah sebanyak 125 karyawan yang bekerja di PT XYZ Jakarta Selatan. Teknik analisis data dalam penelitian ini menggunakan SmartPLS 4.1. Hasil penelitian menunjukkan bahwa work motivation dan work-life balance tidak memiliki pengaruh signifikan terhadap organizational commitment, career development memiliki pengaruh positif dan signifikan terhadap organizational commitment, job satisfaction memiliki pengaruh positif dan signifikan terhadap organizational commitment, work motivation memiliki pengaruh positif dan signifikan terhadap job satisfaction, serta job satisfaction dapat memediasi pengaruh antara work motivation terhadap organizational commitment. Implikasi manajerial dari penelitian ini adalah perlu meningkatkan program pengembangan karir melalui pelatihan berkala, mentoring, dan jalur promosi yang jelas demi komitmen karyawan. PT XYZ perlu melakukan evaluasi kembali terkait sistem kompensasi dan insentif, melibatkan karyawan dalam pengambilan keputusan agar rasa memiliki meningkat, serta perlu memberikan apresiasi atas hasil kerja dan kegiatan kolaboratif untuk meningkatkan makna dan keterlibatan dalam bekerja.